Measurement of the Value for the Economic Benefits from Leisure-An Application of Nested Logit Model - Chich-Ping Hu (International Journal of Architectural Engineering Technology, 2016)
Most of the employees in Taiwan now have two days off per week, increased participations in leisure and sport have raised the utilizing on the environmental resources at maple-watching sites for viewing maple trees. Therefore, a balance policy between environmental conservation and economic growth must be considered. Specifically, what will be the result of removing these maple-watching spots? Comparatively, what is to be gained when leisure activities increase? This study adopts six maple tree viewing sites and uses questionnaires to survey tourist experiences. The Nested Logit model is applied to construct a nested choice structure and estimate the value of economic benefits from leisure and sport using a Random Utility model. Finally, this study shows the economic benefits of leisure participation in these sites and proves that these values will increase by improving each maple tree viewing site’s characteristics. Additionally, various economic benefits are to be derived when the maple tree viewing sites are removed in case of requests from public policy.